Twenty years of research on fungus-microbe-plant interactions on Lyman Glacier forefront – lessons learned and questions yet unanswered - Jumpponen, Ari M.; Brown, Shawn Paul; Trappe, James M.; Cázares, Efrén; Strömmer, Rauni (My University, 2012)
Retreating glaciers and the periglacial areas they vacate for organismal colonization produce a harsh environment of extreme radiation, nutrient limitations, and temperature oscillations. They provide a model system for studying mechanisms that drive establishment and early assembly of communities. Here, we synthesize more than twenty years of research at the Lyman Glacier forefront in the North Cascades Mountains, comparing the results and conclusions for plant and microbial communities. Compared to plant communities, the trajectories and processes of microbial community development are difficult to deduce. However, the combination of high throughput sequencing, more revealing experimental designs, and analyses of phylogenetic community provide insights into mechanisms that shape early microbial communities. While the inoculum is likely randomly drawn from regional pools and accumulates over time, our data provide no support for increases in richness over time since deglaciation as is commonly observed for plant communities. Re‐analyses of existing datasets suggest that microbial, particularly fungal, communities are insensitive to time since substrate exposure from underneath the retreating glacier but responsive to plant establishment both in biomass and community composition. Further research on functional aspects, organismal activity, or ecosystem services in early successional environments will provide deeper appreciation for the dynamics of these communities.
Keywords: Community assembly; Community convergence; Community divergence; Community trajectory; Establishment; Glacier forefront; Mycorrhiza; Propagule